The Increasing of Employee Performance Through Discipline, Motivation, and Organizational Culture - Suwaldiyana Suwaldiyana (INNOVATION RESEARCH JOURNAL, 2021)
The purpose of the study was to determine the effects of the dicipline, motivation,and organizational culltural on imploiyee in PT. Swadaya Graha Gresik samples using to total sample ( total sampling ) on sessus by selecting direc emploiyes as many as 62 people. Data were analysed using multiple liniar regresion. The results of multiple linear regresion anlysis proved that diciplin, motivation and organizational cullture proved to have significant influince partially on the performance of employess at PT. Swadaya Graha Simultaneously dicipline, motivation, and organization culltural are also shown to significantly influense employee performance at PT. Swadaya Graha. These results can be interpreted that by their dicipline, motivation and organization culltural that has been opplied to improve the performance in employees at PT. Swadaya Graha Gresik